Hubungan antara Spiritualitas dengan Kesiapan Lansia dalam Menghadapi Kematian di Panti Sosial Tresna Werdha Sabai Nan Aluih Sicincin - Nabila Hendrasti; Rina Mariana; Harry Theozard Fikri (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
This study aims to see the relationship between the spirituality with the readiness elderly in dealing with death in elderly at the Tresna Werdha Social Home, Sabai Nan Aluih Sicincin. The independent variable in this study is spirituality and the dependent variable is the readiness of the elderly in facing death. The measuring instruments used in this study were the spirituality scale and the elderly readiness scale in facing death. The sampling technique used in this study was purposive sampling with a total sample size of 50 elderly. The validity test uses the Corrected Item-Total Correlation technique and the reliability test uses the Alpha Cronbach technique. The trial results showed the coefficient of spirituality validity ranged from 0.351 to 0.863, while the reliability coefficient was 0.967. The results of the validity coefficient on the readiness scale of the elderly in the face of death were 0.325 to 0.755, while the reliability coefficient was 0.932. Based on the results of data analysis, the correlation coefficient is 0.636 with a significance level of p = 0.000. This means that there is a significant relationship with a positive direction between spirituality and the readiness of the elderly in facing death at the Tresna Werdha Sabai Nan Aluih Sic Ring Social Home. So it can be interpreted that the hypothesis in this study is accepted. With the effective contribution of the spirituality variable to the readiness of the elderly in facing death at the Tresna Werdha Sabai Nan Aluih Sic ring Social Home, it was 40%.